Groundnut Production and Marketing Constraint as Perceived by the Farmers of Wanaparthy District Telangana - Bhavani, Gottemukkula; Koghare, D. T. (International Journal of Economic Plants, 2025)
The present study was conducted during March to June 2021–2022 in Wanaparthy district, of Telangana State. The objective of the study was to investigate and analyse the perceived constraints of the groundnut farmers in this district encounter in both the production and marketing phases. A sample of 120 groundnut farmers within Wanaparthy district was selected for the study. To rank the various constraints, the study utilized Garrett’s ranking technique, a statistical tool designed to provide a clear hierarchy of constraints based on their perceived severity. Data collection was carried out through a pre-tested interview schedule. The results revealed that the most critical constraint farmers faced was the limited access to improved, or pure seed varieties. This was identified as the top-ranked constraint followed by low germination rates of available seeds, which further exacerbated production challenges. Many farmers also reported encountering spurious seeds being sold in the market. Another major constraint highlighted in the study was the inadequacy of extension services provided to the farmers. In response to these findings, the study recommended stronger collaboration between public and private stakeholders to improve seed quality and availability. It stressed the need for certified seeds and better information dissemination to farmers. Additionally, enhancing the export quality of groundnuts was proposed as a way to increase profitability and make agriculture more sustainable and financially viable in the long run.